151: Rotavirus Vaccination in Neonatal Intensive Care Units: Safety and Feasibility. Issue 6 (1st June 2014) - Thrall, S; Gonzales, M; Nhan, C; Lamer, P; Girard, G; Perrault, T; Quach, C
Abstract: BACKGROUND: Rotavirus (RV) is the most common vaccine-preventable cause of gastroenteritis (GE) in children. Currently, RV vaccination of infants in the NICU is not recommended. Infants in the NICU are however at very high risk of complications related to RVGE and a proportion will exceed age-eligibility for the first vaccine dose while admitted. RV vaccination was implemented in 2011 at a tertiary care NICU in response to this problem. OBJECTIVES: We aimed to describe the safety and feasibility of a NICU-based vaccination program against RV. DESIGN/METHODS: The RV vaccination program was implemented in July 2011. Hospitalized infants in a tertiary care NICU who received ≥1 dose of the RV5 vaccine were included. Of 62 infants vaccinated, 36 charts have been reviewed so far. Healthcare-associated (HA) RV cases from April 2009 to March 2013 have been identified through prospective HA infections surveillance and reviewed. RESULTS: Our NICU has an annual average of 393 admissions per year and 7229 patient-days during the study period. Since July 2011, 8.5% of NICU admissions were vaccinated against rotavirus. Twenty-two infants (61%) were males, the vaccinated population had a median gestation age of 33 weeks (IQR 28 6/7 to 38 3/7), a median birth weight of 1740 g (IQR 980 g to 2989 g) and a median length of stay of 79 days (IQR 55 to 110 days). The three main primary diagnostic categories of vaccinated infants were gastrointestinal (n=12), respiratory tract (n=7), and genetic (n=6). Thirty-six first doses, 11 second doses and eight third doses were administered at a median age of 61, 93 and 128 days respectively. Comparing each infant's median feeds in the seven days post-vaccine to their pre-vaccine feeds, there was a median change of +3.5 mL. The incidence rate of HA-RVGE prior to program implementation was 4.86 (95% CI 1.95 to 10) per 10, 000 patient-days; the incidence rate in the intervention period (July 2011 to March 2013) has been 0 (95% CI 0 to 2.54) per 10, 000 patient-days. The incidence rate ratio was 0 (95% CI 0 to 0.69). CONCLUSIONS: There was no case of HA-RVGE after the implementation of our RV vaccination program in our NICU. This study supports the safety and feasibility of a RV vaccination program in NICUs that aims to protect patients with the highest risk of RVGE complications once discharged.